ANALISIS EFEKTIVITAS REALISASI ANGGARAN BELANJA MODAL DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN MUSI BANYUASIN - Rano Asoka (Institut Rahmaniyah Sekayu, 2019)
This research aims to determine the effectiveness of the realization of capital expenditure budget in the Trade and Industry Board of Musi Banyuasin. It has been reached the goal budget target in the government of Musi Banyuasin Regency. The methods of research used are qualitative methods. The data collection techniques used are interview research, documentation, and library studies. Data analysis was conducted using qualitative descriptive analysis methods and the use of capital expenditure budget data and the realization of capital spending in 2016 to 2018. The results showed that The Trade and Industry Board of Musi Banyuasin Regency in realization of the capital expenditure budget in the year 2016 to 2018 can be said to be effective and in positive growth. In 2016 to the year of 2018, The Trade and Industry Board of Musi Banyuasin Regency is still dependent on local government so that the implementation decentralization of capital expenditure budget can be said to be effective.